Body dysmorphic disorder: from clinical aspects to treatment - Carla Alexandra da Silva Carneiro (2021)
Body dysmorphic disorder (BDD), also known as dysmorphophobia, is a relatively common disorder, with a point prevalence of 0.7% to 2.4% among the general population, that consists of a distressing or impairing preoccupation with imagined or slight defects in appearance, associated with repetitive behaviors and where insight regarding the appearance beliefs is often poor. Failure to recognize and diagnose this disorder can lead to poor physical and psychiatric outcomes for patients, thus it is important for the physicians to be aware to the clinical aspects of this disorder, for early detection of the condition and consequently give an appropriate treatment to the patients. The criteria for diagnosing BDD are described according to the DSM-IV and DSM 5. The search for bibliographic information was held on the Pubmed platform with the keywords: body dysmorphic disorder. Only articles that obeyed the following conditions were analyzed: written in English or Portuguese and with free full access; having analyzed 494 articles, between 1994 and 2020. There were included 41 articles that appeared to be relevant for the Body dysmorphic disorder, and which aimed to clarify the clinical, diagnostic and therapeutic aspects of this clinical entity. Serotonin reuptake inhibitors (SRIs) are currently considered the medication treatment of choice. According to all studies conducted do date, for an improvement of symptoms, a relatively high SRI dose and at least 12 weeks of treatment is often needed. The psychosocial treatment of choice is cognitive behavioral therapy. Additional treatment development and efficacy studies are urgently needed to better understand the therapeutic approach of this entity, in order to improve the quality of life of these patients.